Divergent functional traits and gene expression profiles in native and encroaching plant species across an alpine elevational gradient - Yang, Zhongzan; You, Jian; Li, Jiangnan; Zhao, Wei; Xing, Ming; Zhang, Yujiao; Cui, Ma; Gong, Yuqiao; Zhao, Yueming; Chen, Xia (Frontiers in Plant Science, 2025)
IntroductionThe examination of plant adaptive responses to their native habitats amid global climate change is a critical research focus. Alpine tundra ecosystems, with extreme conditions (e.g., low temperatures and nutrient scarcity), present unique challenges to plant survival. This study aimed to explore how plants adapt to the alpine tundra environment, comparing native species and an encroaching species.MethodsWe analyzed 10 native alpine tundra plant species and one encroaching species (Deyeuxia angustifolia) in the Changbai Mountain region. Our approach combined three methods: Morphological characteristic analysis to assess structural adaptations; CSR strategy evaluation (competitive, stress-tolerator, ruderal strategies) to characterize ecological strategies; Comparative transcriptome analysis to reveal molecular mechanisms of adaptation.ResultsNative dwarf shrubs and herbs: activated defense responses, immune responses, and ubiquitous proteins to cope with thermal and oxidative stress. Evolved distinct pathways to adapt to nitrogen deficiency, cold stimuli, and water scarcity. Key proteins (MYC2, ChiB, PI-PLC, Hsp70, POD) drove stress-tolerator (S-related) strategies. Encroaching species (D. angustifolia): efficient adaptation to nitrogen deficiency, tolerance to water deficits, and insensitivity to cold stimuli likely fueled its proliferation in alpine tundra. Transcriptomic insights: traditional stressors (nitrogen deficiency, water deficit, cold) exerted lower transcriptional regulatory pressure on plants than other stressors. Gene expression patterns linked to resource acquisition traits may influence D. angustifolia’s ecological niche expansion in the tundra.DiscussionThis study emphasizes the convergence of plant adaptive adjustments in alpine tundra ecosystems. By integrating morphological, ecological, and molecular data, our findings provide new foundational insights into plant responses to harsh environments—critical for predicting community dynamics under climate change in alpine systems.